1972
DOI: 10.1128/jb.109.3.1232-1238.1972
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Outgrowth of Single Spores of Saccharomyces cerevisiae Viewed by Scanning Electron and Phase-Contrast Microscopy

Abstract: Single spores of Saccharomyces cerevisiae were examined during germination and outgrowth by scanning electron and phase-contrast microscopy. Also determined were changes in cell weight and light absorbance, trehalose utilization, and synthesis of protein and KOH-soluble carbohydrates. These studies reveal that development of the vegetative cell from a spore follows a definite sequence of events involving dramatic physical and chemical modifications. These changes are: initial rapid loss in cellular absorbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
0
1

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 15 publications
6
18
0
1
Order By: Relevance
“…The results presented show that 80% of the trehalose is catabolized during the initial stages of germination with glucose. As has been seen previously (19), some trehalose does remain and may represent a different trehalose pool.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The results presented show that 80% of the trehalose is catabolized during the initial stages of germination with glucose. As has been seen previously (19), some trehalose does remain and may represent a different trehalose pool.…”
Section: Resultssupporting
confidence: 65%
“…rapidly glycolyze trehalose after a burst of oxygen (22). Yeast spores require a carbon source for germination (14), and indeed when supplied with an exogenous carbon source, such as glucose, the endogenous trehalose is rapidly depleted (19). Trehalose accumulation also occurs in yeast during periods of diauxie, and upon transfer to an environment facilitating growth the trehalose is degraded (15,24).…”
mentioning
confidence: 99%
“…5. Protein synthesis, followed by the incorporation of 3H-I,-phenylalanine, began at about 45 min after the onset of germination, (28). After 6 h (Tj in sporulation medium, a sample was withdrawn.…”
Section: Resultsmentioning
confidence: 99%
“…Canada Packers Limited, Toronto 9, Ontario, Canada. succinic acid synthetic medium (SSM) containing 1% Tween 80 (28). Germination and outgrowth were carried out and measured as previously described (28).…”
Section: Methodsmentioning
confidence: 99%
“…These dramatic variations in glycogen and trehalose content, and the large absolute amounts that can be accumulated, suggest that these carbohydrates play important roles during the yeast life cycle. Indeed, studies correlating glycogen and trehalose levels with the physiological and developmental activities of the cells have suggested that these carbohydrates function as important carbon and energy reserves in starving cells (4,7,8,24), in cells undergoing respiratory adaptation (21,26,28,31), in sporulating cells (5,9,15), in germinating spores (15,34), in vegetative cells during emergence from stationary phase in fresh medium (24,39), and in cells traversing the mitotic cell cycle under conditions of carbon and energy limitation (19,20,41). Unfortunately, many of these studies are difficult to interpret in detail because they suffer from one or more of the following limitations: use of a strain that was not well characterized genetically; failure to measure extracellular glucose concentrations; inadequate characterization of the growth-limiting factors in the media used; inadequate characterization of the life cycle status of the cells (particularly the lack of reliable data on cell numbers); failure to measure both glycogen and trehalose; or use of a glycogen assay that seems to give spuriously high values (see Discussion).…”
mentioning
confidence: 99%